Materi Pendidikan Tentang Fiqih Berdasarkan Hadis Tarbawi - Wawan Setiawan; Yuliharti Abbaas (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2022)
This article discusses the tarbawi Hadith regarding the importance of fiqh material.  This research article was compiled using the literature method,  namely collection data from various references, namely E-books, scientific journals,  hadith enclopedias,  articles,  and websites. The purpose of this research In to find out hadith that discuss the importance of fiqh material,  explanations of hadith in general or general syarah of Hadith, chain of hadith, asbabun hadith,  quality of hadith, and analysis of hadith in an educational context.  The hadith under discussion is H.R Bukhori No. 6768 found the results of research on the importance of hadith material fiqh, and this hadith is authentic and is a hadith tafaqquh alaihi.